Leisure and Leisure Education as Resources for Rehabilitation Supports for Chronic Condition Self-Management in Rural and Remote Communities - Hutchinson, Susan; Lauckner, Heidi; Stilwell, Christie; Meisner, Brad A. (Frontiers in Rehabilitation Sciences, 2022)
The potential of leisure (enjoyable free time pursuits) to be a resource for chronic condition self-management (CCSM) is well established. Because leisure pursuits are often self-determined, they have the potential to allow people to not only address self-management goals (e.g., managing symptoms through movements or stress-reducing activities) but meet important psychosocial needs (e.g., affiliation, sense of mastery) as well as support participation in a range of meaningful life situations. In this ‘Perspective’ piece, we advocate for the ways leisure and leisure education can be resources for rehabilitation professionals to support CCSM, especially in rural and remote communities. In particular, we focus on aspects of the Taxonomy of Everyday Self-Management Strategies (TEDSS ) to highlight ways that embedding leisure and leisure education into supports for CCSM can strengthen rehabilitation services offered to rural and remote dwelling adults living with chronic conditions. Recognizing the breadth of leisure-related resources available in rural and remote communities, we recommend the following strategies to incorporate a focus on leisure-based self-management within rehabilitation services: a) enhance the knowledge and capacity of rehabilitation practitioners to support leisure-based CCSM; b) focus on coordinated leadership, patient navigation, and building multi-sectoral partnerships to better link individuals living with chronic conditions to community services and supports; and c) educate individuals with chronic conditions and family/carers to develop knowledge, skills, awareness and confidence to use leisure as a self-management resource.